Proximité et démarches participatives à l’Isle-aux-Grues et l’Isle-aux-Coudres (Québec) - Julie Guillemot (Territoire en Mouvement)
This paper discusses the development of two insular territories on the Saint Lawrence River (Quebec): Isle-aux-Grues and Isle-aux-Coudres where the implementation of participatory approaches are studied. We use the analysis of proximity relationships between actors to describe the social and spatial context within which these participatory approaches are inserted. This analysis exposes insular specificities. These specificities are an advantage (notably through proximity logics that happen) as well as a constraint (high degree of interpersonal relationships that weigh on approaches, conflicts of use, difficulty of openness to new migrants) to the development of these territories. The participatory approaches studied favored the opening of new spaces of dialogue between actors. This was supported by preexisting proximities (territorial identity, professional links) and generated new ones (networking, common objective). Nevertheless, some proximity relationships such as social and sectorial cleavages or isolation can become constraining and limit the scope of these approaches.